2018
DOI: 10.1177/2056305118787520
|View full text |Cite
|
Sign up to set email alerts
|

To Serve and to Tweet: An Examination of Police-Related Twitter Activity in Toronto

Abstract: Police departments across North America and Europe are using Twitter for many different reasons, one of the most important being public relations (i.e., image work). This article examines the relationship between Twitter use, police image work, and public engagement in the Canadian context. On the basis of 8,174 police-related tweets sent by the Toronto Police Service (TPS) and citizens, we advance the argument that despite its dialogical potential, the TPS use Twitter first and foremost as a means to legitimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 43 publications
1
35
1
Order By: Relevance
“…As Brainard and Edlins (2015) note, this is in part because the police often fail to fully engage with, or even respond back to, a communicative public. Similarly, although only examining one police service, Kudla and Parnaby (2018) found that interaction with citizens via the Toronto Police Services (TPS) Twitter account was mainly used to solidify the legitimacy of TPS. Nevertheless, from the limited research that exists, these types of interactive posts appear to generate the most public interest (e.g., comments and likes) (Lieberman et al, 2013).…”
Section: Social Media As Image Workmentioning
confidence: 99%
“…As Brainard and Edlins (2015) note, this is in part because the police often fail to fully engage with, or even respond back to, a communicative public. Similarly, although only examining one police service, Kudla and Parnaby (2018) found that interaction with citizens via the Toronto Police Services (TPS) Twitter account was mainly used to solidify the legitimacy of TPS. Nevertheless, from the limited research that exists, these types of interactive posts appear to generate the most public interest (e.g., comments and likes) (Lieberman et al, 2013).…”
Section: Social Media As Image Workmentioning
confidence: 99%
“…for a law enforcement group indicated citizen memberships had a significant increase of 22 to 184% by each district. The style and demeanor of communication was reported as more than likely having a significant effect with respect to the data (see also Kudla & Parnaby, 2018). According to Brainard and McNutt, the findings indicated the departments' relationships with the public resembled an old public administration style of interaction.…”
Section: Bureaucratic Versus Interpersonal Style Of Communication With the Publicmentioning
confidence: 79%
“…Researchers such as Derrick-Mills (2011), Ching andHand (2011), and Kudla and Parnaby (2018) expect SM implementation of holding the possibility to fundamentally alter the interactions and relationships between the government and the populace; however, Kingsley (2012) does not agree. According to Kingsley, the government's use of SM has been viewed as merely a way to emphasize services the city offers, plus websites and SM continue to be an avenue for information distribution.…”
Section: Bureaucratic Versus Interpersonal Style Of Communication With the Publicmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, by emphasizing interactions between individuals and authorities, rather than the wider community, citizens remain detached and do not engage in collective action, outcomes lacking the consensual and deliberative qualities of more robust community‐oriented approaches (Terpstra, ). Finally, participation is often fictively democratic, with the police strictly controlling interactions and citizens being unable to substantively influence and steer decision‐making (Kudla & Parnaby, ; Schneider, ).…”
Section: Social Media and The Police Management Of Visibilitymentioning
confidence: 99%